Impact of the EU Packaging and Packaging Waste Regulation on the Finnish beverage industry - Artjoki, Otto (My University, 2025)
The European Union’s Packaging and Packaging Waster Regulation (PPWR) adopted in 2024 introduces new sustainability requirements aiming to reduce packaging waste by promoting circular economy practices in a variety of industries. Ready to consume packaged beverages sold in retail, a considerable source of packaging waste, is one of the impacted industries. The aim of this study is to examine the impact of PPWR on the Finnish beverage industry from a supply chain perspective, focusing on how industry stakeholders plan to meet the regulation’s requirements. A qualitative research using semi-structured interviews was conducted in order to reach the research objectives. First, a literature overview on circular economy of beverage packaging was performed. The reuse targets and recycled content requirements of PPWR, which are judged to impact the beverage industry the most were then explored. A theoretical framework was built from the interface of the studied literature and regulation, which served as the basis for the interview questions. Three interviews of industry experts were conducted. The interviewees represented relevant stakeholders of the industry, including grocery retail, packaging and beverage manufacturing and deposit return system (DRS) administration. The insight from the interviews was then gathered and summarized in a solution framework. Impacts and solutions concerning stakeholder collaboration and individual stakeholders are presented in the solution framework. The findings indicate that PPWR’s reuse targets and recycled content requirements will significantly affect supply chain operations in the Finnish beverage industry. Implementing a reuse system requires considerable investments from industry stakeholders. The financial burden of the required investments is asymmetrical due to limited capability of small-scale producers to invest in efficient equipment. The reverse logistics of used containers to the correct manufacturer is a challenging due to local market conditions. Operating reuse systems increases the administrative burden of industry stakeholders. Recycled content requirements may cause availability issues of single-use plastic bottles if the recycling rate of other industries is not increased. Collaboration of industry stakeholders is found to be crucial in the implementation and operation of environmentally and economically efficient reuse systems. DRS with an accessible network of collection facilities is considered to be an effective way to promote high return rates of reusable containers. The co-ownership of DRS operators enables the alignment of interests, facilitating collaboration. The centralization of reuse cycle steps and standardization of beverage packaging is found to decrease logistical complexity and to promote environmental and cost-efficiency. However, competitive behaviour and conflicting interests of industry stakeholders may limit the willingness of economic operators to collaborate. The main driver of the solutions that economic operators plan to employ to comply with sustainability regulations is identified to be business needs rather than sustainable values of companies. Legislators should therefore design sustainability legislation in a manner where business needs and environmental goals are parallel. Legislative vagueness is found to limit the planning of stakeholders. Clarity and preparedness should be pursued in legislation to support stakeholder planning.

Euroopan unionin vuonna 2024 hyväksymä pakkaus- ja pakkausjäteasetus (PPWR) asettaa lukuisille toimialoille uusia kestävän kehityksen vaatimuksia, joiden tavoitteena on vähentää pakkausjätteen määrää edistämällä kiertotalouskäytäntöjä. Juomateollisuus, joka on merkittävä pakkausjätteen lähde, on toimiala, jota uudet vaatimukset koskevat. Tämän tutkimuksen tavoitteena on selvittää toimitusketjuvaikutuksia, joita PPWR:llä on Suomen juomateollisuuteen ja identifioida ratkaisuja, joita alan eri sidosryhmät suunnittelevat hyödyntävänsä asetuksen vaatimusten noudattamiseen. Tutkimus suoritettiin laadullisena tutkimuksena. Aineistonkeruumenetelmänä käytettiin puolistrukturoituja haastatteluita. Haastattelukysymykset pohjautuvat tutkimuksen teoreettiseen viitekehykseen, joka luotiin kirjallisuuskatsauksen ja asetuksen relevanttien osien tarkastelun pohjalta. Tutkimuksessa suoritettiin kolme haastattelua alan asiantuntijoiden kanssa. Haastateltavat edustivat eri juomateollisuuden sidosryhmiä, kuten päivittäistavarakauppaa, pakkaus- ja juomateollisuutta sekä panttijärjestelmän ylläpitäjää. Aineiston keruun ja analyysin pohjalta saadut tulokset esitetään ratkaisuviitekehyksessä, joka käyttää tutkimuksen teoreettista viitekehystä pohjanaan. Tutkimuksen tulokset osoittavat, että PPWR:ssä esitetyt juomapakkausten uudelleenkäyttötavoitteet ja sisältövaatimukset vaikuttavat Suomen juomateollisuuden toimitusketjuihin merkittävästi. Uudelleenkäyttöjärjestelmän implementointi edellyttää alan toimijoilta mittavia sijoituksia laitteistoon, joka kuormittaa pienempiä toimijoita suhteellisesti enemmän. Juomapakkausten paluulogistiikka on paikallisten markkinaolosuhteitten takia haastavaa. Uudelleenkäyttöjärjestelmä lisää hallinnollista kuormaa. Kertakäyttöisten muovipullojen sisältövaatimukset saattavat aiheuttaa saatavuushaasteita, ellei muiden toimialojen kierrätysastetta saada nostettua. Sidosryhmien välistä yhteistyötä voidaan tulosten pohjalta pitää välttämättömänä taloudellisesti tehokkaan ja kestävän uudelleenkäyttöjärjestelmän luomisessa. Panttijärjestelmä kattavalla keräyspisteverkostolla on tehokas menetelmä edistää uudelleenkäytettävien pakkausten palautumista kuluttajilta. Panttijärjestelmän ylläpitäjän yhteisomistajuus eri sidosryhmien kesken tunnistetaan toimivaksi tavaksi yhteensovittaa risteäviä intressejä ja edistää yhteistyötä. Paluulogistiikan prosessien keskittäminen ja juomapakkausten standardisointi vähentää logistista monimutkaisuuta edistäen uudelleenkäyttöjärjestelmän kestävyyttä ja kustannustehokkuutta. Toisaalta sidosryhmien kilpailullinen toiminta ja risteävät intressit rajoittavat sidosryhmien halukkuutta yhteistyöhön. Tutkimuksen tulosten mukaan yrityksen liiketoiminnalliset intressit ohjaavat yritysten päätöksentekoa vastuullisuussääntelyn noudattamisessa enemmän kuin yrityksen vastuulliset arvot. Vastuullisuussääntelyssä tulisikin ottaa tämä huomioon, ja pyrkiä yhteensovittaa liiketoiminnalliset intressit vastuullisuustavoitteiden kanssa. Lainsäädännön epäselvyyden ja keskeneräisyyden havaittiin myös rajoittavan yritysten kykyä valmistautua uusia vaatimuksia varten. Sääntelyssä tulisikin tavoitella yritysten suunnittelun tukemiseksi selkeyttä.
Keywords: circular economy, reuse system, packaging, sustainability, EU, legislation, supply chain management, kiertotalous, uudelleenkäyttö, pakkaukset, vastuullisuus, EU, lainsäädäntö, toimitusketjujen johtaminen